Elite Universities and the Intergenerational Transmission of Human and Social Capital - Andres Barrios-Fernandez; Christopher A. Neilson; Seth D. Zimmerman (Institute of Labor Economics (IZA), 2024)
Do elite colleges help talented students join the social elite, or help incumbent elites retain their positions? We combine intergenerationally-linked data from Chile with a regression discontinuity design to show that, looking across generations, elite colleges do both. Lower-status individuals who gain admission to elite college programs transform their children's social environment. Children become more likely to attend high-status private schools and colleges, and to live near and befriend high-status peers. In contrast, academic achievement is unaffected. Simulations combining descriptive and quasi-experimental findings show that elite colleges tighten the link between social and human capital while decreasing intergenerational social mobility.
Keywords: I24; D64; J62; 330; elite universities; intergenerational mobility; human capital; social capital